CALCULATION OF SHAFT DIAMETER AND EFFECTIVENESS FACTOR OF FRONT WHEEL BRAKES ON YAMAHA VIXION 150 CC - Rafiq Allam Mutaqin; Viktor Naubnome; Ratna Dewi Anjani (Universitas Muhammadiyah Semarang, 2022)
In technology that is currently very advanced, especially in the field of engineering or automotive, there are many types of motorcycles and each has its advantages and disadvantages. The more advanced the technology, the more different motorcycles from time to time starting from fuel economy, increased engine performance and other supporting technologies, motorcycles are required to be operated or run on various road conditions. However, the engine that functions as the prime mover on a motorcycle cannot do well what the road conditions require or demand. For example, when the road is climbing, a motorcycle requires a large torque (torque) but the speed or speed of the motorcycle required is low. In planning the engine elements this time, the author will calculate the diameter of the shaft and the effectiveness factor as well as the actual braking time on the front wheel disc brakes of the 2014 Yamaha Vixion 150 cc motorcycle, which is one of the engine elements. An axle and brake must have a proper and sturdy construction to support the load and keep the engine speed to function properly and the brake effectiveness factor must also be following what has been planned. From the calculation results obtained, the diameter of the shaft specification on the Yamaha Vixion 150cc motorcycle is 17 mm while the diameter of the calculation is 16.33 mm and the effectiveness factor of the front disc brake of the Yamaha Vixion 150cc is 0.60.Keywords: Technology, Shaft diameter, Effectiveness factor, Disc brake